2021
DOI: 10.1177/00033197211047329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sacubitril/Valsartan Combined with Dapagliflozin on Long-Term Cardiac Mortality in Heart Failure with Reduced Ejection Fraction

Abstract: The angiotensin receptor–neprilysin inhibitor (ARNI) sacubitril/valsartan and sodium-glucose cotransporter-2 (SGLT-2) inhibitor dapagliflozin have been shown to reduce rehospitalization and cardiac mortality in patients with heart failure (HF) with reduced ejection fraction (HFrEF). We aimed to compare the long-term cardiac and all-cause mortality of ARNI and dapagliflozin combination therapy against ARNI monotherapy in patients with HFrEF. This retrospective study involved 244 patients with HF with New York H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Hongbo Yang et al found that phase standard deviation and bandwidth negatively correlated with LVEF in chronic total occlusion (CTO) lesions, while the skewness and kurtosis of the phase map positively correlated with LVEF [ 20 ], which is consistent with our findings. Note that LVEF is a powerful predictor of cardiac mortality [ 21 ]. Our study showed that the worse left ventricular mechanical contraction synchrony leads to decreased LVEF, making the systolic synchrony parameters valuable in the prediction of cardiac mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Hongbo Yang et al found that phase standard deviation and bandwidth negatively correlated with LVEF in chronic total occlusion (CTO) lesions, while the skewness and kurtosis of the phase map positively correlated with LVEF [ 20 ], which is consistent with our findings. Note that LVEF is a powerful predictor of cardiac mortality [ 21 ]. Our study showed that the worse left ventricular mechanical contraction synchrony leads to decreased LVEF, making the systolic synchrony parameters valuable in the prediction of cardiac mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the results revealed that, compared with ARNI monotherapy, the risk of a patient having heart failure hospitalization 3,4,8,9 was significantly reduced by the combination therapy [risk ratio ¼ 0.65, 95% CI (0.53-0.79), Z ¼ 4.23, P < 0.001], the result from both RCTs [risk ratio ¼ 0.62, 95% CI (0.47-0.81), Z ¼ 3.49, P < 0.001] and cohort studies [risk ratio ¼ 0.69, 95% CI (0.52-0.93), Z ¼ 2.44, P ¼ 0.01], respectively. The risk of cardiovascular death 3,4,8 was also significantly reduced by the combination therapy [risk ratio ¼ 0.65, 95% CI (0.46-0.93), Z ¼ 2.37, P ¼ 0.02], especially the result from the only cohort study [risk ratio ¼ 0.38, 95% CI (0.16-0.87), Z ¼ 2.30, P ¼ 0.02]. In addition, the risk of a patient having all-cause death 3,4,8,9 was significantly reduced by the combination therapy [risk ratio ¼ 0.70, 95% CI (0.54-0.92), Z ¼ 2.59, P ¼ 0.01], especially the results from two cohort studies [risk ratio ¼ 0.59, 95% CI (0.36-0.95), Z ¼ 2.18, P ¼ 0.03] (Fig.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…The risk of cardiovascular death 3,4,8 was also significantly reduced by the combination therapy [risk ratio ¼ 0.65, 95% CI (0.46-0.93), Z ¼ 2.37, P ¼ 0.02], especially the result from the only cohort study [risk ratio ¼ 0.38, 95% CI (0.16-0.87), Z ¼ 2.30, P ¼ 0.02]. In addition, the risk of a patient having all-cause death 3,4,8,9 was significantly reduced by the combination therapy [risk ratio ¼ 0.70, 95% CI (0.54-0.92), Z ¼ 2.59, P ¼ 0.01], especially the results from two cohort studies [risk ratio ¼ 0.59, 95% CI (0.36-0.95), Z ¼ 2.18, P ¼ 0.03] (Fig. 3 and Table 3).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Combination therapy of sacubitril/valsartan therapy with SGLT2 inhibitors—originally developed as anti-diabetic drugs—has shown additional benefits in patients with diabetic cardiomyopathy ( Kim et al, 2021 ; Karabulut et al, 2022 ). The combination exhibits synergistic effects through independent mechanisms that offer greater prominent improvements in cardiac function, observed with the augmented LVEF and reduction in E/E’ ratio, as well as a decrease in the risk of cardiovascular death.…”
Section: Mechanistic Roles Of Sacubitril/valsartan In Cardiac Remodelingmentioning
confidence: 99%
“…In addition, sacubitril/valsartan improves fractional shortening, cardiac output, loaddependent indices of left ventricular contractility (dp/dt max ), and relaxation (dp/dt min ) in animal heart failure models (Maslov et al, 2019b;Ge et al, 2020;Liu Y. et al, 2021;Raj et al, 2021) (Table 2). Combination therapy of sacubitril/valsartan therapy with SGLT2 inhibitors-originally developed as anti-diabetic drugs-has shown additional benefits in patients with diabetic cardiomyopathy (Kim et al, 2021;Karabulut et al, 2022). The combination exhibits synergistic effects through independent mechanisms that offer greater prominent improvements in cardiac function, observed with the augmented LVEF and reduction in E/E' ratio, as well as a decrease in the risk of cardiovascular death.…”
Section: Effects On Cardiac Functionmentioning
confidence: 99%